Efektifitas Promosi Online Pada E-Commerce Di Indonesia - Deshinta, Hana; Suyanto, Ama (LPPM Institut Bisnis dan Informatika Kesatuan, 2020)
By the development of era, there's increasing someone's mindset to create an innovation, which one is the promotion is right on the target. Nowadays, performer of e-commerce apply some promotion to get the market. e-commerce's competing eachother to create an inovation by promotion, for maintain the market and increase the users. There is various kinds of online promotions available on today, but the effectiveness of online promotions is not yet known to be applied by e-commerce. The purpose of this study is to determine the effectiveness of online promotions. The research uses the EPIC Model Test which has 4 dimensions, namely empathy, persuasion, impact and communication. This study uses non-probability sampling because the population does not allow members of the population to have the same opportunity to be selected as a sample. This study also uses data collection techniques by distributing questionnaires. Through the distribution of questionnaires to 426 respondents in Indonesia who use e-commerce. The results was found that the Empathy of dimension is a very effective way for online e-commerce promotion. Followed by the Persuasion dimension, the Impact dimension and the Communications dimension. Overall results according to all four dimensions show that online promotion is effective in the e-commerce industry. Keywords : E-Commerce, Online Promotion, EPIC Model